The impact of political affiliation on support for gun control among Hispanic police officers - Luo, Fei (Journal of ethnicity in criminal justice, 2025)
Gun control remains a central issue in the U.S., yet studies on support for gun control among Hispanics and police officers are limited. This study examines Hispanic police officers’ support for gun control in a department near the US-Mexico border, with a focus on the impact of political affiliation and other instrumental factors. Data from 241 officers were collected via face-to-face and online surveys. Structural equation modeling results revealed that political affiliation is a significant predictor of police officers’ support for gun control. Compared to respondents who identified as Democrats, officers who self-identified as Republicans were significantly less likely to support gun control. A variety of other factors such as generation status, punitiveness, and right-wing authoritarianism have been found to be associated with police officers’ attitudes toward gun control. The study highlights policy implications based on these findings.